Quantifying the world : UN ideas and statistics - Ward, Michael (United Nations intellectual history project., 2004)
Good data, Michael Ward argues, serve to enhance a perception about life as well as to deepen an understanding of reality. This history of the UN's role in fostering international statistics in the post-war period demonstrates how statistics have shaped our understanding of the world. Drawing on well over 40 years of experience working as a statistician and economist in more than two dozen countries around the world, Ward traces the evolution of statistical ideas and how they have responded to the needs of policy while unravelling the question of why certain data were considered important and.